Hubungan antara Keterampilan Manajerial Kepala Sekolah dan Iklim Organisasi dengan Kinerja Guru - Sulistyorini Sulistyorini (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Correlation between the Principal's Managerial Skill and Organizational Climate and Teachers' Performance. This research was conducted to examine the correlation between the principal's managerial skill and organizational climate and teachers' performance. The sample consisted of 125 physical education teachers and principals in Kabupaten Mojokerto. A questionnaire was used to collect data, which were then analyzed statistically by regression analyses. The result indicated that there was a significant correlation between the managerial skill and organizational climate and the teachers' performance. The performance of teachers graduated from sport teacher schools was better than those graduated from non-sport schools.